Some correlates of non-insulin dependent diabetes mellitus in a rural population in Khon Kaen province, Northeast Thailand - Darasavong, Kongkeo
To study about the magnitude and some correlates of non-insulin diabetes mellitus (NIDDM), the data obtained from a population-based cross-sectional study on nutritional status and serum lipids of a rural population in Northeast Thailand was used. The study was conducted in three districts of Khon Kaen province, in 1995.The objectives of this study was firstly, estimate the overall prevalence as well as age and sex specific prevalence of NIDDM; secondly to determine the strength of the relationship between NIDDM and family history of diabetes, body mass index (BMI), and triglycerides. Three hundred and twenty-three subjects, 135 males and 188 females, aged between 30-68 years, were included in this study.The results have shown that the overall prevalence of NIDDM of the subjects was 13.3. The disease was more common in males than in females with prevalence of 15.6for males and 11.7for females. The disease prevalence increased with age, with prevalence of 5.8for the young age adilt, 16.5for the middle age adult, 15.0for the older age, and 22.2for the oldest age group.In unvariate and also in multivariate analysis, body mass index and triglycerides were positively and significantly associated with NIDDM. While family history of diabetes seems to have a protective effect on having NIDDM, this relationship could be explained by chance.In the logistic regression analysis, the probability of having NIDDM among the obese subjects (BMI = 25.00 kg/m?) was about twice more than the normal nutritional status group (BMI 25.00 kg/m?) (POR CI = 1.04-4.72). The odds of having disease among those with high triglyceride level (triglycerides 200 mg/dl) was about five times more than the normal triglyceride level group (triglycerides = 200 mg/dl) (POR = 5.75; 95CI = 2.66-12.40). The odds of having disease amnong those with family history of diabetes was about one-third compared with those who did not have family history (POR=0.36; 95CI=0.07-1.69).Health education for preventive measures on reducing over-nutrition and increasing physical activity is recommended.